A legislação pós-conquista: a análise da imagem de Fernando III, o Santo (1201–1252) como instrumento de ensino e pesquisa. - Siqueira, Saymon Da Silva (2023)
In this work, we aim to present and discuss the procedural aspects that make up the construction of the digital learning object Conquest of Córdoba (available at: https://conquista-de- cordoba.netlify.app/), based on the study of Iberian medieval sources, namely: Chronica regum Castellae and the Fuero de Córdoba. Concerning these sources, it is worth noting that the Chronica focuses on the reigns of Alfonso VIII (1155-1214), Enrique I (1204-1217), and Fernando III (1201-1252), concluding the narrative after the conquest of Córdoba. The Fuero, on the other hand, is a production of the Fernandine chancery from the year 1241, containing 58 rubrics to organize the occupation and maintenance of the conquered territory. Based on this documentary corpus, we conducted a postgraduate research project titled "Post-conquest legislation: the analysis of the image of Ferdinand III, the saint (1201-1252) as a tool for teaching and research" to understand the power mechanisms and their various strategies employed by the Fernandine regency to conquer and reorganize the Kingdom of Córdoba and, subsequently, Andalusia. Supported by this research, we developed a digital LO with the purpose of providing tools for teaching History in basic education and promoting the dissemination of medieval history to non-academic audiences. Therefore, in this work, we will reflect on the challenges, relevance, and potential connections of an LO of this nature based on the proposed framework.